Effect of nitrogen fertilizer regulation on rice panicle morphology, yield and economic benefits under low-temperature stress - Du, Xiaojing; Zhang, Yanhong; Hou, Tianyu; Zhao, Zhiqiang; Li, Dong; Kang, Mintai; Wen, Xiaorong; Tang, Fusen; Abliz, Buhaliqem; Qi, Yuhong; Yuan, Quan; Yuan, Jie; et al. (Frontiers in Plant Science, 2025)
IntroductionThis study aimed to determine the optimal nitrogen (N) application rate for mitigating low-temperature (LT) stress damage at different growth stages and to elucidate the underlying mechanisms in rice cultivation in Xinjiang.MethodsA split-plot field experiment was conducted in 2024 using the rice cultivar ‘Xinjing 8’. The main plots included three temperature environments: control (CK), lowtemperature stress at the tillering (TLS), and low-temperature stress at the jointing stage (JLS), perform a 3-day LT treatment at 16°C. Subplots were assigned five N application rates: 295.5, 267.9, 240.3, 212.7, and 0 kg·ka-1. The effects of N rate on rice panicle traits, yield, and economic benefits under these growing environments were evaluated.ResultsThe results indicated that under lowtemperature stress, rice exhibited significant reductions in panicle weight, plant height, number of secondary branches, effective panicles, and grain yield per panicle, particularly during the jointing stage. Nitrogen supplementation under low-temperature stress significantly improved rice tillering and panicle traits, simultaneously elevating grain yield and economic benefits. Specifically, at optimal nitrogen application rate of 267.9 kg ha-1, the crop yields under TLS and JLS treatments were 4424.40 and 2350.82 kg ha-1. At the same N application rate, a positive net income was achieved only in the CK treatment.DiscussionThis study identifies a nitrogen application rate of 267.9 kg ha-1 as an effective measure to mitigate low-temperature stress-induced limitations on rice panicle development, resulting in enhanced yield and economic gains. Consequently, it provides a practical solution for advancing sustainable rice cultivation in coldprone regions such as Xinjiang.